RETRACTED: Establishment of Criteria for Molecular Differential Diagnosis of MPLC and IPM - Wang, Xiaohui; Gong, Yuan; Yao, Jianfei; Chen, Yan; Li, Yuemin; Zeng, Zhen; Lu, Yinying; Song, Lele (Frontiers in Oncology, 2021)
Backgrounds Differential diagnosis of multiple primary lung cancer (MPLC) and intrapulmonary metastasis (IPM) is one difficulty in lung cancer diagnosis, and crucial for establishment of treatment strategies and prognosis prediction. This study aims to establish the criteria for molecular differential diagnosis of synchronous MPLC and IPM by the next-generation sequencing (NGS) method. Methods Training cohort included 30 synchronous MPLC (67 samples) patients and 5 synchronous IPM (13 samples) patients with adenocarcinoma. Criteria of MPLC/IPM differential diagnosis were established by results from a NGS-based 605-gene panel test. Subsequently, 16 patients (36 samples) were recruited as the validation cohort to verify the criteria. Results IPM lesions showed a high degree of mutation overlap with an average concordance rate of 60.2% (range: 15.8%–91.7%). IPM lesions had at least three common alterations, including both high-frequency driver gene alterations and low-frequency gene alterations. In contrast, the average concordance rate of MPLC was 11.0% (range: 0.0%–100.0%), among which 66.7% (20/30) of patients had no common alterations (concordance rate: 0%). In the remaining 10 patients, 9 had only one overlapping alteration while 1 had two overlapping alterations, in which 6 patients had EGFR L858R overlapping mutation. Alterations were classified into trunk, shared, and branch subtypes. Branch alterations accounted for 94.4% of mutations in MPLC, while accounted for only 45.0% in IMP. In contrast, the ratio of trunk (38.3%) and shared (16.7%) alterations in IPM was significantly higher. The criteria for differentiating MPLC from IPM using 605-gene panel was established: 1) MPLC can be interpreted if no overlapping alterations is found; 2) MPLC is recommended if one overlapping high-frequency drive gene alteration and/or one overlapping low-frequency gene alteration are/is found; 3) IPM can be interpreted if more than three common alterations are found. Subsequently, 16 patients were recruited as the validation cohort in the single-blind manner to verify the criteria, and 14 MPLC and 2 IPM were identified, which was 100% consistent with the results from independent imaging and pathological diagnosis. Conclusions NGS detection can distinguish synchronous MPLC from IPM and is a useful tool to assist differential diagnosis.